Investigating the Associations of Constructivist Beliefs and Classroom Climate on Teachers' Self-Efficacy Among Australian Secondary Mathematics Teachers - Guangbao, Fang; Timothy, Teo (Frontiers in Psychology, 2021)
This study examines the associations of constructivist beliefs and classroom climate on teachers’ self-efficacy in instruction, classroom management, and student engagement among Australian secondary mathematics teachers. To do this, it uses the integrated model of teachers’ self-efficacy with the concept of analysis of teaching tasks. The study uses structural equation modeling to analyze data from 495 mathematics teachers in the Teaching and Learning International Survey (TALIS) 2013. The results reveal the integrated model is a valid theoretical framework to explain Australian secondary mathematics teachers’ self-efficacy. Teachers’ constructivist beliefs and classroom climate are positively and statistically significantly related to teachers’ self-efficacy in instruction, classroom management and student engagement. In contrast, constructivist beliefs have no significant correlation with classroom climate.